2010
DOI: 10.1166/jnn.2010.2044
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Zinc Oxide Nanoparticles for Biophotonics

Abstract: A novel Zinc oxide (ZnO)-Hydrogel fluorescent colloidal semiconductor nanomaterials system is presented for potential bio-medical applications such as cell and tissue imaging. ZnO nanoparticles (NPs) synthesized using arc discharge technique has been conjugated to bio-compatible Poly N-isopropylacrylamide (PNIPAM) based hydrogel polymer matrix. The stability and fluorescence of ZnO nanoparticles are significantly enhanced using hydrogel colloidal dispersion. Photoluminescence spectroscopy indicates approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 15 publications
3
12
0
1
Order By: Relevance
“…This NP may also be swallowed directly through food bundling or medication delivery (14,15). Emamifar et al demonstrated that zinc (Zn) ions considerably migrate in low-density polyethylene (LDPE) nanocomposite packaging (16).…”
Section: Introductionmentioning
confidence: 99%
“…This NP may also be swallowed directly through food bundling or medication delivery (14,15). Emamifar et al demonstrated that zinc (Zn) ions considerably migrate in low-density polyethylene (LDPE) nanocomposite packaging (16).…”
Section: Introductionmentioning
confidence: 99%
“…ZnO NPs are being used in the food industry as additives and in packaging due to their antimicrobial properties (Gerloff et al 2009;Jin et al 2009). They are also being explored for their potential use as fungicides in agriculture (He at al., 2010] and as anticancer drugs and imaging in biomedical applications (Rasmussen et al 2010;John et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…ZnO NPs are added to various materials and products, for example, plastics, glass, ceramics, rubber, cement, paints, lubricants, ointments, sealants, adhesives, batteries, pigments, ferrites, and fire retardants. Furthermore, ZnO nanometals have ultraviolet (UV)-shielding, deodorizing impacts, antibacterial properties, impact and heat and UV light resistance, which could afford a great potential for its widespread use in many fields including cosmetics and sunscreens [6], fungicides in agriculture [9], food additives and additives in packing [7,8], and biomedical uses such as anticancer drugs [10,11]. Nanoparticles are highly reactive due to their small size as well as high surface area.…”
Section: Introductionmentioning
confidence: 99%